Evaluation of Achievement of Overburden Production Target Using Fishbone Diagram Method at Pit A Site B PT XYZ, South Sumatera Province - Aurah Masyitha Ayu Namira; Aryanti Virtanti Anas; Rizki Amalia; Rini Novrianti Sutardjo Tui (EPI International Journal of Engineering, 2021)
PT XYZ is one of the companies engaged in the coal mining and energy in South Sumatra Province. Mining activities at the Pit A are still focused on stripping overburden using the Komatsu PC-3000E power shovel digging tool. The company has established a 513,333 BCM production target of overburden stripping in November 2020. While the total overburden production obtained is 488,162 BCM. The existence of factors that affect the productivity of the tool will determine the achievement of production targets, so it is necessary to evaluate production by identifying the factors causing the problem. One of method that can be used to determine the root cause of the problem is by using a fishbone diagram. A Fishbone diagram is a method used to identify the root cause of a quality problem. The purpose of this research is to calculate overburden production in November 2020, identify factors that influence the achievement of overburden production targets using a fishbone diagram, and make recommendations for improvement plans based on factors that affect the achievement of overburden production targets. Based on the results of the fishbone diagram analysis using the 4M pattern consisting recommendations for improvement plans can be designed for each factor causing the problem which is machine, methods, materials, and manpower.